Piranha solution treatment: A facile method for improving the antithrombotic ability and regulating smooth muscle cell growth on blood contact materials - Liao, Yuzhen; Chen, Xiao; Jiang, Yutong; Qu, Chao; Liu, Xiaoqi; Zhao, Ansha; Yang, Ping; Huang, Nan; Chen, Jiang (Frontiers in Bioengineering and Biotechnology, 2023)
Blood contact materials require strong anti-fouling capabilities to avoid thrombus formation. Recently, TiO2-based photocatalytic antithrombotic treatment has gained focus. Nevertheless, this method is restricted to titanium materials with photocatalytic abilities. This study offers an alternative solution that can be applied to a broader range of materials: piranha solution treatment. Our findings revealed that the free radicals generated by the treatment effectively altered the surface physicochemical properties of various inorganic materials, enhancing their surface hydrophilicity and oxidizing organic contaminants, thus improving their antithrombotic properties. Additionally, the treatment resulted in contrasting effects on the cellular affinity of SS and TiO2. While it significantly reduced the adhesion and proliferation of SMCs on SS surfaces, it significantly enhanced these on TiO2 surfaces. These observations suggested that the impact of the piranha solution treatment on the cellular affinity of biomaterials was closely tied to the intrinsic properties of the materials. Thus, materials suitable for piranha solution treatment could be selected based on the functional requirements of implantable medical devices. In conclusion, the broad applicability of piranha solution surface modification technology in both blood-contact and bone implant materials highlights its promising prospects.